RAPPORT: ESSENTIAL HARMONIOUS FACTOR IN LANGUAGE CLASSROOM - Fitrawati, Fitrawati (English Department FBS UNP, 2010)
This article discusses on how teachers build and establish the harmonious environment between them and their students. This term is called as rapport. The writer has collected some theories from some experts about how to establish rapport in the language classroom. In the line with the experts opinions, it is very important for teachers to maintan the rapport in their classroom. Understanding rapport in more depth, it can be said that it has to do with appreciating where other people are coming from, understanding their point of view and seeking to develop and maintain a connection with them. It is suggested that teachers can apply the strategies given in this articles because by doing so teachers can take benefit of establishing rapport from their class room. The strategies to establish rapport in language classroom are: getting to know the students both inside and outside of the classroom, learning student names as quickly as possible, considering non-verbal factors such as body language, developing a relationship built on trust, having a sense of humor and having fun with students